READY FOR THE HOME GAME? THE SURFACE NAVY AND HOMELAND DEFENSE - Miller, Joshua C. (Monterey, CA; Naval Postgraduate School, 2022)
Strategically, it will always be preferable for the United States to fight “out there” where the conflict is far away from the homeland. But, as the Russian and Chinese navies continue to develop longer-range capabilities and other threats toward the U.S. homeland grow, it is crucial to examine how well the surface Navy is prepared to defend the homeland. Given both the emerging threats from peer competitors, such as Russia and China, and the surface Navy’s prioritization of forces abroad, this thesis asks whether the surface Navy is adequately prepared to defend against such future threats to the American homeland. Through a qualitative analysis of relevant literature, this thesis concludes that the American homeland will be targeted by peer competitors during a future crisis or conflict. Based on credible threats to the homeland, the Navy will have to balance appropriately on prioritizing and allocating forces abroad and at home. The Navy will have to break away from the traditional maritime strategy of primarily only fighting abroad, and it will need to provide assistance to enhance a layered defense approach to effectively defend the homeland in the future. Thus, this thesis recommends establishing a national combined maritime and aerospace defense command to ensure that air, land, and sea forces are prioritized and allocated appropriately for the defense of the American homeland during crisis or conflict in the future. Approved for public release. Distribution is unlimited. Lieutenant, United States Navy